MODEL INOVASI TATA KELOLA SEKOLAH GRATIS (STUDI DI SEKOLAH MENENGAH KEJURUAN NAHDLATUL ULAMA TENGGARANG KABUPATEN BONDOWOSO): SMK NU TENGGARANG BONDOWOSO - DARIS WIBISONO SETIAWAN DAN INDAH MEI ASTUTI (Mitra Pendidikan, 2022)
Research on the innovation model of free school governance which is the initiation of educational institutions has never been carried out by researchers, especially from the perspective of public administration. Previous research was only on the issue of the implementation of a policy product. This free school innovation governance model research is important, especially if it is associated with the following two facts. First, based on the results of previous research studies that there is no research that describes the implementation of free schools at the SMK/SMA education level which is an innovation from these educational institutions. However, there have been many results of research on the implementation of public policies in the field of education with the research locus being schools or regions only based on the policy umbrella it is implementing. Second, the education gap in Indonesia is very large. The education gap is the gap between the size of the education budget that has been provided by the state and the limited access to education related to school financing. Researchers in this study to achieve research objectives using qualitative methods with the research locus at a private vocational education institution, namely SMK NU Tenggarang. The aims of this study are: (1) to analyze the governance model for institutional development at SMK NU Tenggarang; (2) analyzing the governance model of free school administration at SMK NU Tenggarang; and (3) designing an innovation model for the administration of free schools at SMK NU Tenggarang. Data collection techniques used in this study were interviews, observation and documentation. The researcher determined key information sources (Key Informants), namely the principal and supporting information sources (supportive informants) consisting of the head of the foundation, supervisors of the SMK Branch of the Bondowoso Regional Education Office, school committees, teachers, students, employees, parents of students. Data analysis consists of three flow of activities that occur simultaneously, namely data reduction, data presentation, and drawing conclusions. The data validity technique uses source triangulation techniques, method triangulation, key informant reviews, and data base preparation. The results of the study conclude that: First, transformational leadership based on the strength of the doctrine is the main dimension of strengthening governance for the development of SMK NU Tenggarang institutions. Second, transparency, openness, and internal commitment strengthen the principles of education governance and encourage the birth of free school innovation. Third, the SI RETA free school governance innovation model was born from transformational leadership based on the strength of the doctrine by prioritizing the principles of transparency, openness, and internal commitment.